Mixed pretreatment based on pectinase and cellulase accelerates the oil droplet coalescence and oil yield from olive paste. (1st February 2022) - Huang, Meigui; Huang, Shuai; Wang, Qiang; Hayat, Khizar; Ahmad, Mehraj; Ying, Ruifeng; Hussain, Shahzad
Graphical abstract: Highlights: Combined pretreatment of cellulase and pectinase destroyed olive cell wall structure. Decreased viscosity of olive paste promoted the oil droplets aggregation. Mixed enzymatic pretreatment enhanced the oil yield (4.4%, w/w) from olive paste. Abstract: Commercial enzymatic pretreatment is being classically used for enhancing the oil extraction yield in the olive oil industry in China. Nevertheless, the mechanism is not yet clearly defined. The aim was to study the action of pectinase and cellulase for improving the oil yield from the aspects of oil droplets coalescence and rheological properties changes of olive paste during malaxation process. From confocal laser scanning microscopy imaging, the bound oil droplets were released and gradually coalesced into larger droplets, eventually formed a continuous oil phase with enzymatic pretreatment. Furthermore, the mixed enzymatic pretreatment effectively decreased viscosity of the olive pastes and promoted the depolymerization and solubilization of pectic polymers involved in the cell-cell adhesion, thus further enhanced the oil extraction yield from 7.15 % to 11.68 % (w/w). Finally, the mixed enzymatic pretreatment improved the droplet release and coalescence, reduced the viscosity of olive paste, and increased the oil yield.